International Congress on Applications of Lasers &Amp; Electro-Optics 2017
DOI: 10.2351/1.5138187
|View full text |Cite
|
Sign up to set email alerts
|

Build-up strategies for additive manufacturing of three dimensional Ti-6Al-4V-parts produced by laser metal deposition

Abstract: Laser metal deposition (LMD) has been applied as a coating technology for many years. Today, the technologies capacity to produce 3D depositions leads to a new field of application as additive manufacturing method. In this paper, 3D laser metal deposition of titanium alloy Ti-6Al-4 V is studied with special regard to the demands of additive manufacturing. Therefore, only the coaxial LMD powder nozzle is used to create the shielding gas atmosphere, which ensures high geometric flexibility. Furthermore, specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Spranger et al [107] also reported interdependencies between the inter-layer time and the melt pool geometry for laser metal deposition of Ti6Al4V. Low inter-layer times resulted in distinct heat accumulation, higher initial temperatures of the build plane, broader melt tracks and reduced layer heights.…”
Section: Fig 13mentioning
confidence: 98%
“…Spranger et al [107] also reported interdependencies between the inter-layer time and the melt pool geometry for laser metal deposition of Ti6Al4V. Low inter-layer times resulted in distinct heat accumulation, higher initial temperatures of the build plane, broader melt tracks and reduced layer heights.…”
Section: Fig 13mentioning
confidence: 98%
“…This becomes increasingly significant in tall parts with high heat capacity. Therefore, the phenomenon was initially investigated for processes such as laser metal deposition (LMD) [ 9 ] and wire-arc-based AM process (WAAM) [ 10 ], where typical part sizes are larger than LPBF. More recently, it has been studied for the LPBF process as well.…”
Section: Introductionmentioning
confidence: 99%
“…So, not only should mechanical properties of repaired parts meet the requirements but also the fatigue crack propagation rate (FCPR) need meet the predetermined standard. 12,13 Once the crack rapidly propagates, there are serious consequences to the normal service of aircrafts, which makes it necessary to study the fatigue crack propagation behavior of TA15 by repaired. In addition, the fatigue crack behavior of titanium alloy is closely related to microstructure.…”
Section: Introductionmentioning
confidence: 99%